Towards X-as-Models in the Context of CI/CD - Teumert, Sebastian; Tegeler, Tim (Electronic Communications of the EASST, 2025)
The X-as-Code approach has seen much success over the last few decades because it leads to reliably reproducible outcomes and can be used to automate a wide variety of workflows. However, it still suffers from the problem that it requires textual configurations that require expertise in the system and its conventions to be used, as well as extensive documentation. In this paper, we highlight Xas- Models as an alternative paradigm that offers the same advantages of reproduceability and automation, but allows domain experts to configure the workflow in an intuitive, low-code/no-code way by simply manipulating self-documenting graphical models. By employing Language-driven Engineering (LDE) and allowing for the interaction of multiple Purpose-specific Languages (PSLs), which can all be edited in the same environment (modeling IDE, mIDE), X-as-Code offers a holistic approach to creating workflows that connect multiple tools and environments together. Additionally, we stipulate that such models can be used for static analysis and can be checked for correctness in a more abstract way than platform-specific textual configurations. As demonstration of this approach, we use the domain of CI/CD and build on our previous work on modelling CI/CD workflows in a graphical way. We highlight how we can leverage our experience and the knowledge gained from creating this platform-specific tool (supporting only GitLab) to identify a core semantic for the whole domain of CI/CD and then leverage this higher abstraction for validation, static analysis and runtime monitoring of the CI/CD process itself.